Dendrocalamus melanotrichus (Poaceae, Bambusoideae), a new bamboo species from Yunnan, China - Li, Jian-Wei; Sun, Mao-Sheng; Bao, Hao-Feng; Hui, Chao-Mao; Liu, Wei-Yi (Phytotaxa, 2026)
Dendrocalamus melanotrichus, a new woody bamboo endemic to Yunnan, China, is described and illustrated. The new species is morphologically similar to D. puerensis, D. atroviridis, D. menghanensis and D. hookeri, but differs in the following character combination: culm leaf sheaths densely covered with black setae and shoulders with oral setae, reflexed culm leaf blade, culm leaf auricle with 5 mm long oral setae, and 5–10 mm tall culm leaf ligule with a deeply dentate margin. Based on its branch complement with 1–3 dominant branches, branching from lower culm nodes, and inconspicuous culm leaf auricles, this new species is assigned to D. subg. Dendrocalamus.